STUDY OF CHILD PROTECTION FOR SEXUAL EXPLOITATION THROUGH CYBERPORN - Hervina Puspitosari (UNTAG Law Review, 2019)
Technological developments have changed human behavior that brings both positive and negative impacts. Misuse of information technology is characterized by the development of cybercrime and the increasingly widespread cases of cyberporn. Especially cyberporn which involves children as victims so that there needs to be attention from the government to protect children from the circulation of cyberporn and become victims of irresponsible cyberporn business people by exploiting children. Sexual crime and exploitation of children through cyber are now so troubling that prevention efforts are needed so that children do not become more victims so that the government, family, community and law enforcement must pay close attention. The perpetrators are using technological sophistication through digital cameras and cell phones and social media to capture potential child victims of cyberporn crime. Photos of the child can be quickly published on the internet.